ANALYSIS OF GRADE XI SCIENCE TEXTBOOKS IN HIGH SCHOOL BASED ON ASPECTS OF SCIENTIFIC LITERACY - Fadhilah Aulia Tribuanadewi; Hendro Pranoto (Universitas Negeri Medan, 2022)
Textbook plays a crucial role in enhancing students' scientific literacy skills. This study aims to evaluate the level of scientific literacy in the biology textbook for Grade XI based on four aspects: scientific knowledge, nature of scientific inquiry, science as a way of thinking, and the interaction between science, technology, and society. Three biology textbooks for Grade XI used in the Medan Tembung district, North Sumatra, were randomly selected, namely Bumi Aksara, PT Tiga Serangkai, and Grafindo Media Pratama. The results of the study indicate that the proportions of scientific literacy aspects in these three textbooks are unbalanced. The aspect of scientific knowledge shows a good percentage (81.42% for Bumi Aksara, 72.90% for PT Tiga Serangkai, and 70.88% for Grafindo). However, the aspects of the nature of scientific inquiry, science as a way of thinking, and the interaction between science, technology, and society have poor percentages for all evaluated textbooks. Therefore, the appropriate selection of textbooks by teachers is crucial in improving students' scientific literacy skills.